ENHANCING VISUAL INTELLIGENCE USING 3D E-WORKSHEETS WITH THINK PAIR SHARE ON MOLECULAR SHAPES - Maria Regina Caile Ardamis; Sukarmin (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2026)
The understanding of molecular form materials requires a high level of visual spatial skills, but most high school students still show low visual intelligence since the content is abstract and there isn't any interactive digital media. The goal of this project is to enhance students' visual intelligence regarding the submaterial of molecular shapes by creating 3D-assisted e-worksheets that are integrated with the Think Pair Share (TPS) paradigm. The 4D model (define, design, develop) is used in this development research. involving 35 students in grades XI-3 of SMA Hang Tuah 1 Surabaya and three expert validators. Data was collected through validation sheets, response questionnaires, activity observation sheets, and visual intelligence pretest-posttests including four indicators: imagination, conception, problem solving, and pattern search. The results showed that the e-worksheets were declared valid with all ≥ 4 medians, practical with 96.43% student responses and 99.4% activity implementation, and effective according to the Wilcoxon Signed-Rank test (Z = −5.165, p = 0.000) with an average increase of 56.90 points and all students experienced an increase in scores. The highest increase occurred in the pattern search indicator (64.24 percentage points). 3D-assisted electronic worksheets integrated with TPS have proven to be effective in bridging abstract molecular representations with students' visual intelligence, so they can be an alternative learning medium for abstract chemistry materials at the high school level.